PRAKTIK MANAJEMEN LABA UNTUK MENURUNKAN BEBAN PAJAK - Dharayanti, Ni Wayan Pertiwi (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to determine whether the earnings management practices conducted by companies are motivated to reduce tax expenses. Earnings management practices are proxiedby discretionary accrual. Motivation taxation indicated by changes in the value of net deferred tax liabilities are divided into two groups which are the group practices earnings managementto reduce the tax expense and vice versa. Population and sample is public companies in Indonesia listed in the Indonesia Stock Exchange. The results of data analysis show that firmsin Indonesia do earnings management practices to increase profits, but is not motivated to reduce tax expenses. Keywords: Earnings Management, Tax Management, Net Deferred Tax Liabilities